Globally Constructed, Locally Mediated: Indonesian Millennial Mothers' Experiences in Shaping the Global Narrative of Disney Princesses - Rivga Agusta; Annisa Gissena (Ikatan Sarjana Komunikasi Indonesia, 2025)
This study explores the experiences of Indonesian millennial mothers in mediating Disney princess narratives as information hegemony from media giants. Aiming to understand how parental mediation shapes children's interpretations of global princess constructions, the study highlights how mothers address the intersection between global media influences and local cultural values. Using a phenomenological approach, in-depth interviews with four purposively selected mothers were conducted to uncover how they actively mediate Disney princess content through various media forms, such as films, books, and merchandise. The study reveals that media giants like Disney construct dominant cultural narratives that mothers, as cultural mediators, can reinforce or challenge, reflecting societal ideologies and shaping children's understanding of global narratives. By examining the role of parents in managing media consumption, the study highlights the impact of information hegemony on children's media exposure and identity formation. Ultimately, this study contributes to understanding the negotiation between corporate media influences and local cultural contexts, emphasizing the power of parental agency in shaping children's media literacy and critical engagement with global narratives.